Cities in motion : urban life and cosmopolitanism in Southeast Asia, 1920-1940 - Lewis, Su Lin, 1979- (Cambridge : Cambridge University Press, 2016)
'In the 1920s and 1930s, the port cities of Southeast Asia were staging grounds for diverse groups of ordinary citizens to experiment with modernity, as a rising Japan and the growth of American capitalism challenged the predominance of European empires after the First World War. Both migrants and locals played a pivotal role in shaping civic culture. Moving away from a nationalist reading of the period, Su Lin Lewis explores layers of cross-cultural interaction in various spheres: the urban built environment, civic associations, print media, education, and popular culture. While the book focuses on Penang, Rangoon, and Bangkok - three cities born amidst British expansion in the region - it explores connected experiences across Asia and in Asian intellectual enclaves in Europe. Cosmopolitan sensibilities were severely tested in the era of post-colonial nationalism, but are undergoing a resurgence in Southeast Asia's civil society and creative class today'--
'Asian Connections is a major series of ambitious works that look beyond the traditional templates of area, regional or national studies to consider the trans-regional phenomena which have connected and influenced various parts of Asia through time. The series will focus on empirically grounded work exploring circulations, connections, convergences and comparisons within and beyond Asia'--
Includes bibliographical references : (pages 273-299) and index.
Keywords: Port cities -- Southeast Asia -- History -- 20th century; Cosmopolitanism -- Southeast Asia -- History -- 20th century; Sociology, Urban -- Southeast Asia -- History -- 20th century; Southeast Asia -- Civilization -- 20th century; Southeast Asia -- History -- 20th century